The Tendencies of the Internal and External Migration of the Republic of Armenia - Chakhoyan, Gagik (Journal of Sociology: Bulletin of Yerevan University, 2017)
In this paper, main determinants of internal and external migration from the communities of Armenia were reviewed. Based on the Human capital model of migration, ordinary regression models, as well as spatial econometrical models were estimated, particularly spatial autoregressive model and spatial error model. Geographically weighted regression was estimated in order to show the distribution of the determinants of migration on the map.
Keywords: migration, territorial development index, human capital model of migration, spatial autocorrelation, spatial autoregressive model, spatial error model, geographically weighted regression